Multivariate analysis of metal contamination in street dusts of Istanbul D-100 highway - (:unkn) unknown (SOC BRASILEIRA QUIMICA, 2008)
Metals are found in street dust especially in big cities, like Istanbul. This is a significant contribution to the environmental pollution. For this purpose, fifty six samples of Istanbul street dust were collected for metal contamination analysis in the period of December 2003 to April 2004. The mean concentration of Pb, Zn, Ni, Cd and Cu determined by graphite furnace atomic absorption spectrometry were found to be 368.3, 431.2, 27.1, 0.3 and 191.1 mu g g(-1) respectively. Metal values in street dust samples were several times higher than the control. Correlations among the different metal concentrations were calculated. Multivariate statistical analyses ( principal component analysis - PCA and cluster analysis - CA) were applied to the data matrix to determine the analytical results and to identify the possible origin of metals in these dusts. The results indicate that Pb, Zn, Cd, Ni and Cu are mainly originated from anthropogenic sources.
Keywords: trace metals; Istanbul; street dust; road transport; PCA; SOILS